Revision of Maryland Minor Consent Law on Human Immunodeficiency Virus Infection Prevention: An Outcome of Advocacy - Oluwatosin Olateju; Deb Dunn; Patricia McLaine; Sharon Barrett (HIV/AIDS Research and Treatment-Open Journal, 2020)
Objectives To date, only few United States (US) states have explicit regulations that allow minors to independently give consent for human immunodeficiency virus infection (HIV) prevention treatments. This manuscript will reflect upon key advocacy efforts leading to the revision of the Maryland Minor Consent Law, evaluate current human immunodeficiency virus infection and acquired immune deficiency syndrome (HIV/AIDS) prevention laws for minors in U.S. states, and highlight resources for health advocacy. Methods Between 2018-2019, public health professionals in Baltimore, Maryland reviewed the Maryland Minor Consent Law and other adolescent consent laws within the U.S. The professionals advocated for a legal review of the gap by the State Senate and the Office of Attorney General. Results In May 2019, the public health advocates were successful in their effort for a revision of the Maryland Minor Consent Law to include Treatment for the Prevention of HIV-Consent by minors. Upon their review of all adolescent consent laws within the U.S., they found that only eleven states currently have explicit language indicative of an adolescent’s ability to give consent for pre-exposure prophylaxis (PrEP). Conclusion This inquiry can change upstream factors such as laws, regulations, policies and institutional practices.